Fictionalizing Fiction through the Metaphor of (De)Construction in Kamel Daoud’s Meursault, contre-enquête - Mary Poteau-Tralie (Studies in 20th & 21st Century Literature, 2019)
Kamel Daoud’s Meursault, contre-enquête, employs the metaphor of (de)construction to disassemble and reconstruct Albert Camus’s L’Étranger on both the plot and lexical levels. Daoud creates a series of binary oppositions using Camus’s original building blocks. His literary rebuilding on the unsteady canonical foundation ultimately valorizes plurality in the retrospective reconstruction of Algeria’s past, and in an ever-deferred construction of its future. Daoud thus becomes inextricably part of the rebuilding process.
Keywords: Kamel Daoud; Meursault; contre-enquête; Camus; deconstruction; postcolonial; L’Étranger; Algeria